Evolution of Electrothermal Heating and Dielectric Properties of Phenolic Resins During Pyrolysis - Aniela J. K. Wright; Smita S. Dasari; Ramu Banavath; Sayyam Deshpande; Ethan M. Harkin; Kailash Arole; Anubhav Sarmah; Micah J. Green (Macromolecular Materials and Engineering, 2025)
Abstract Electrothermal heating generated via radio frequency (RF) fields is used to probe the transformation of phenolic resin to a carbon matrix during pyrolysis. Phenolic resin is a single‐stage thermoset that is popular due to its heat resistance, chemical resistance, high strength, and low creep properties. When phenolic resin is subjected to high‐temperature, low‐oxygen treatment (pyrolysis), it is converted to a carbon material useful for many structural applications. Here, neat phenolic resin is pyrolyzed at different temperatures, and the heating response of the newly formed carbon material is tracked when exposed to an RF field. The electrical conductivity of the matrix increased with increasing pyrolysis temperature, with ≈10−4 S m−1 for the neat sample prior to pyrolysis, and ≈102 S m−1 for the sample pyrolyzed at 850 °C. The material's electrothermal response to applied RF fields increases as the material pyrolyzes and becomes conductive; however, at high pyrolysis temperatures, the material becomes sufficiently conductive such that the RF fields are reflected rather than absorbed, and the heating response decreases. The findings of this work show that heating response to RF fields can be used as a quick and easy characterization technique for tracking structural changes associated with phenolic pyrolysis.